Commercialisation of communal cattle -production systems in the Musekwa valley - Mafukata, Mavhungu Abel (University of the Free State, 2012)
This study was conducted among 55 (n=55) randomly selected communal cattle farmers in the Musekwa Valley of the Limpopo Province, South Africa. The farmers were interviewed using closed and open-ended questions as part of a structured questionnaire-based survey. Thirty key informants were further profiled and interviewed using both closed and openended questions. The main objective of the study was to investigate the constraints on and the opportunities for the commercialisation of communal cattle-production systems in the study area. The specific objectives were to characterise both the communal production systems and also the cattle farmers. The study further estimated the productivity of the communal cattleproduction systems and additionally measured the degree of participation of cattle farmers in the mainstream formal cattle-marketing activities in the study area. The results of the study revealed that all the interviewed communal cattle farmers in the study area did indeed farm in a communal land-use system. In addition, the results revealed that the majority of the communal cattle farmers in the study area were old, lacked proper formal school education, had poor basic literacy, and lacked entrepreneurial and animal husbandry skills that constrained commercialisation of this particular cattle-production subsector. The descriptive results of the study revealed the majority of the communal cattle farmers in the study area to be poor adopters of banking (52.7%), animal breeding (74.1%), farm insurance (100.0%), loans and credit (92.7%), private land (100.0%), own transport (94.5%), commodity marketing (60.0%) and membership of formal farmer organisations (80.0%). The empirical results of the study revealed that 60.0% of these particular cattle farmers were probably not productive, while only 40.0% were probably productive. The majority of the cattle farmers are currently still largely subsistence orientated in that the results revealed that 56.4% of the farmers were selling their animals through informal marketing channels and only 43.6% were selling through formal marketing channels. Cattle production, productivity and mainstream formal cattle marketing are mainly constrained by these farmers' poor access to cattle-production inputs, meagre household endowments, poor adoption of modern technologies, lack of on- and off-farm infrastructure, inadequate skills in animal husbandry and the weak institutional support provided to them. Furthermore, the empirical results revealed that distance to the mainstream formal cattle market, the poor keeping of farm records, cattle ownership and weaning of calves had the most significant impact on farm productivity and on mainstream formal cattle-market participation among the farmers. Among the opportunities revealed by the results of the study were the current pro-poor agricultural policy developed by the South African government specifically to reform and commercialise the communal agricultural systems, good farmer experience regarding cattle production, the existing formal cattle-marketing options and the willingness of farmers to adopt new cattle-production and -marketing technologies and skills. Measured on the Agricultural Commercialisation Continuum (ACC), the cattle-production systems in the study area displayed some increased characteristics of a highly subsistence oriented agricultural production system.

Hierdie studie is uitgevoer onder 55 (n=55) ewekansig-geselekteerde bestaanskommunale veeboere van die Musekwa Vallei in die Limpopo Provinsie van Suid-Afrika. Onderhoude is met dié boere gevoer aan die hand van oop en geslote vrae wat deel was van 'n gestruktureerde, vraelysgebaseerde opname. Die profiele van dertig sleutelinformante is opgestel, waarna onderhoude met hulle gevoer is aan die hand van oop en geslote vrae. Die hoofdoelwit van die studie was om ondersoek in te stel na die beperkinge op en die geleenthede vir die kommersialisering van kommunale veeproduksiestelsels in die studiegebied. Die spesifieke doelwitte was die tipering van sowel die kommunale produksiestelsels as die veeboere. Verder het die studie die produktiwiteit van die kommunale véeproduksiestelsels beraam, asook die mate waarin veeboere deelgeneem het aan die hoofstroom, formele veebemarkingsaktiwiteite in die studiegebied. Volgens die bevindinge van die studie het al die kommunale veeboere in die studiegebied met wie onderhoude gevoer is inderdaad by wyse van 'n kommunale grondgebruikstelsel geboer. Die bevindinge het ook getoon dat die meerderheid van die kommunale veeboere in die studiegebied oud was, 'n gebrek aan behoorlike formele skoolonderrig gehad het, oor swak basiese geletterdheid beskik het en 'n gebrek aan entrepreneuriese en veeteeltvaardighede gehad het wat die kommersialisering van hierdie besondere veeproduksiesubsektor aan bande gelê het. Die beskrywende bevindinge van die studie het aangedui dat die meerderheid van die kommunale veeboere in die studiegebied nie van banke (52.7%), diereteling (74.1%), plaasversekering (100.0%), lenings en krediet (92.7%), private grond (100.0%), eie vervoer (94.5%), kommoditeitsbemarking (60.0%) en lidmaatskap van formele landbou-organisasies (80.0%) gebruik gemaak het nie. Die empiriese bevindinge van die studie het aan die lig gebring dat 60.0% van hierdie spesifieke veeboere waarskynlik nie produktief was nie, terwyl slegs 40.0% waarskynlik was. Die meerderheid van die veeboere is tans steeds grootliks bestaansgeoriënteerd deurdat die bevindinge aangetoon het dat 56.4% van die boere hul diere deur middel van informele bemarkingskanale en slegs 43.6% deur middel van formele bemarkingskanale verkoop het. Veeproduksie, produktiwiteit en hoofstroom formele veebemarking word veral aan bande gelê deur hierdie boere se gebrekkige toegang tot veeproduksie-insette, die karige beskikbaarheid van huishoudelike middele, ontoereikende aanvaarding van moderne tegnologieë, die gebrek aan op-die-plaas- of weg-van-die-plaasinfrastruktuur, onvoldoende veeteeltvaardighede en die swak institusionele ondersteuning wat aan hulle voorsien word. Die empiriese bevindinge het verder aangetoon dat afstand na die hoofstroom formele veemark, gebrekkige byhou van plaasboekhouding en ontoereikende tegnologieë ten opsigte van vee-eienaarskap en die speen van kalwers die mees betekenisvolle impak op boere se plaasproduktiwiteit en op hoofstroom formele veemarkdeelname gehad het. Van die geleenthede wat tydens die studie aan die lig gekom het, was die huidige landboukundige beleid gemik op armes wat deur die Suid-Afrikaanse regering ontwikkel is met as spesifieke oogmerk die hervorming en kommersialisering van die kommunale landboukundige stelsel, 'n positiewe ervaring deur die boer aangaande veeproduksie, boere se goeie ervarings in verband met veeproduksie, die bestaande formele veebemarkingsopsies en boere se bereidwilligheid om nuwe veeproduksie en -bemarkingstegnologieë en -vaardighede toe te pas. Gemeet aan die Landboukundige Kommersialiseringskontinuum, het die veeproduksiestelsels in die studiegebied enkele eienskappe vertoon van 'n landboukundige stelsel wat in 'n hoë mate bestaansgeoriënteerd is.
Thesis (Ph.D. (Centre for Development Studies))--University of the Free State, 2012
Keywords: Communal cattle farmer; Market participation; Commercialisation; Agricultural commercialisation continuum (ACC); Agricultural commercialisation roadmap (ACR); Transaction costs; Productivity; Loan; Farmer organisations; Cattle trade -- South Africa -- Limpopo; Cattle -- Economic aspects -- South Africa -- Limpopo